A Feasibility Study on the Establishment of M3’s Putomansiin Foresthill, Novaliches, Quezon City (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2019)
People nowadays prefer eating meat, fish and pork but not vegetables. The researcher made this research to challenge those people who prefer to eat sweets, fish, and meat than vegetables. This can also be our challenge to apply the learnings of our chosen career and also a guide on learning the possible outcomes of our product called "Rice cake with golden lime" the researchers thought of using golden lime as the main ingredient for the products because it has a lot of nutrients that can help in the good condition of our health that is why we chose the Golden lime as our main ingredient. The method that the researchers used is survey method to gather information by giving questionnaires to the respondents. This method is easy to graph and also easy to analyze. The business called “Putomansi” is feasible based on the survey of the study that researchers made. The total layout and a minimal investment is needed. The demand for this product rises due to the fact that it is a basic necessity for the customers to look for an affordable snack particularly which that matches to their budget and at the same time oversees good health among the consumers. Most of the customers are not familiar with the product so the uniqueness is the key for the product to be sold easily. Most people nowadays live by using social media so our product will easily be known by using social media. According to the survey,, 100% of the respondents liked the new version of Puto Mansi and 100% also liked the uniqueness of our packaging. The distribution shows that based on the findings, 70% of the respondents like the pork as the filling of the puto while 30% likes chicken. 100%of the respondents also said that they will recommend the new version of Puto to their friends and relatives. According to the Feasibility Study about Puto Macapuno, it has been established as part of the Filipino Cuisine and Culture especially during special occasions.
Keywords: M3’s putomansi, feasibility study, BCP